THE TRAINING PROCESS OF A BRAZILIAN BASKETBALL HIGH PERFORMANCE MASCULINE TEAM: AN ANALYSIS OF THE REAL TIME DESTINED TO THE DEVELOPMENT OF THE CONTENTS. (Fiep Bulletin - online, 2015)
Introduction: The actions that a coach assumes in function of the management of the time in training sessions appear as a quality pointer assuming direct influence in the performance of the team. Objectives: The present study desires to investigate concerning the management of the offered time during the training sessions of a high performance adult masculine basketball team. It is intended to verify the useful time destined to the development of each proposal category. Methodology: A study of case with a descriptive format was developed through a reduced and adapted version of direct comment system in court, where categories had been codified using the register of offered useful time for each one of them in diverse sessions of trainings of the planning.  Data: The average duration of the training sessions was of 7117,77 (DP ± 253.71) seconds. The average duration for category in seconds was: EA: 1406,39, PIO: 1764.05, PC A/D: 2825.86, PNE:  893,34, OU: 486,83. For PID the average time was of 1307.  Conclusions: Two main aims had been emphasized: the game tactics structure (strategies) and the maximization of the individual offensive techniques. The team analyzed for this study, when it will be acting, will concentrate its forces in offensive potential. However, in games where the percentage of field goal shooting, will be below of the foreseen one, the defeat probability will be real ahead of the difficult found in relation to training the defense techniques. When it will be necessary to use the defensive potential in order to break the qualities of the adversary, the failure possibilities and lose becomes bigger that of victory.
Keywords: Time Management - Coach Basketball.